A Cognitive Stylistic Analysis of Catharsis Used by Husseini Preachers - Basim Jubair Kadhim; Mujtaba Mohammedali Yahya Al-Hilo (RIRAI Publisher, 2021)
This study deals with catharsis as a cognitive stylistic device used to expel fear and anxiety for the sake of changing the audience toward better by preachers in Husseini discourse – Hussein is a grand Shiite Muslim leader. It aims to explicate the exploitation of catharsis by Husseini preachers and the conceptualization of such phenomenon by the audience. The study adapts the emotion model developed by Kovecses (2000); five stages are utilized: cause of the emotion, emotion, control, loss of control, and behavioral response. Twenty Husseini sermons are analyzed according to the stages of the model. Consequently, the study has come up with considerable conclusions. Chief among them are: Husseini preachers pragmatically use prosodic features to convey catharsis. A further conclusion is that catharsis is utilized by Husseini preachers as a strategy to teach the audience all the objectives of the Husseini revolution and to connect the objectives to this age for the sake of reform, using the fear that can modulate the human behavior.